FORMS OF SEXISM AGAINST WOMEN IN LUCIA PRIANDARINI’S PENYALIN CAHAYA NOVEL: SARA MILLS’ CRITICAL DISCOURSE ANALYSIS - Bourbon, Ade Amelia; Abidin, Aslan; Saguni, Suarni Syam (Media Inovasi Pendidikan dan Publikasi, 2025)
This study aims to analyze the representation of forms of sexism against women in Lucia Priandarini’s Penyalin Cahaya novel through the perspective of Sara Mills’ Critical Discourse Analysis (CDA). The phenomenon of sexual violence, which is rooted in sexism within Sara Mills' framework, is a crucial issue that needs to be critically examined through discourse analysis in literary works. The research employs a qualitative descriptive method using the literature study technique, where data consisting of textual quotations and narration from the novel are analyzed using Sara Mills' CDA. The findings reveal that sexism against women is divided into two primary forms. First, physical sexism (or overt sexism) is manifested through the objectification of women’s bodies, pornography, and sexual harassment, functioning as a tool to assert male dominance and control over women’s bodies. Second, verbal sexism (or indirect sexism) is found in the forms of sexist labeling, gender stereotypes in language, and sexist jokes. Overall, the findings conclude that sexism in the Penyalin Cahaya novel operates as a discursive mechanism that effectively maintains and reinforces the patriarchal power structure, with language and action being used as instruments of control that demean and restrict women's roles. This analysis can serve as a reference for enhancing critical awareness regarding sexist discourse in contemporary literary texts.